Explosive felsic eruptions on ocean islands: A case study from Ascension Island (South Atlantic) - Katie Preece (Journal of Volcanology and Geothermal Research, 2021)
Ocean island volcanism is generally considered to be dominated by basaltic eruptions, yet felsic products associated with more hazardous explosive eruptive events are also present in the geological record of many of these islands. Ascension Island, recently recognised as an active volcanic system, exhibits explosive felsic eruption deposits but their age, eruptive styles and stratigraphic association with mafic volcanism are thus far unclear. Here we present a felsic pyroclastic stratigraphy for Ascension Island, supplemented by 26 new 40Ar/39Ar ages and whole rock geochemical XRF data. More than 80 felsic pyroclastic eruptions have occurred over the last ~ 1 Myr, including subplinian and phreatomagmatic eruptions, which produced pumice fall and pyroclastic density current deposits. Detailed sampling suggests felsic events are unevenly distributed in space and time. Subaerial activity can be divided into four Periods: Period 1 (~1000 – 500 ka) felsic and mafic eruptions, with felsic explosive eruptions, linked to a Central Felsic Complex; Period 2 (~ 500 – 100 ka) mafic period; Period 3 (~ 100 – 50 ka) felsic eruptions associated with the Eastern Felsic Complex; Period 4 (< 50 ka) mafic eruptions. The last explosive eruption occurred at ~ 60 ka. This work highlights the cyclical nature of ocean island volcanism and the timescales over which changes between predominantly mafic and felsic volcanism occur. The prevalence of past felsic explosive eruptions on Ascension highlights the need to consider the possibility of future subplinian or phreatomagmatic events in hazard management plans, with any potential risk compounded by Ascension’s small size and remote location.